Modelling fault reactivation and fluid flow around a fault restraining step‐over structure in the Laverton gold region, Yilgarn Craton, Western Australia. Issue 2 (23rd December 2012) - Zhang, Y.; Schaubs, P. M.; Sheldon, H. A.; Poulet, T.; Karrech, A.
Abstract Laverton is an important region in the Yilgarn Craton for gold mineralization. Previous studies suggested that the premineralization structure was dominated by a fault restraining step‐over structure with the Wallaby fault and Sunrise Shear Zone as the key fault splays hosting the world‐class Wallaby and Sunrise Dam gold deposits, respectively. Two major gold mineralization phases occurred during two of a series of tectonic events with different far‐field stress orientations. 3D coupled deformation and fluid flow modelling was used to investigate the effects of varying far‐field stress orientations on reactivation of the fault structure in the region. The results show that structural reactivation is sensitive to regional shortening directions. Two shortening directions are identified to be favourable for reactivation of the Wallaby fault and Sunrise Shear Zone: (i) NW–SE shortening and (ii) ENE–WSW to E–W shortening. The reactivated segments exhibited localization of shear strain and dilation as well as fluid focusing at locations corresponding to the Wallaby and Sunrise Dam deposits. This is in contrast to the models with shortening direction between NNW–SSE and NE–SW, which showed little fault reactivation at both locations. These results support previous independent interpretations of the controls on gold mineralization at Laverton. The two shortening directions favourable for structural reactivation inferred from the models are consistent with the kinematics of the two main gold mineralization events in the region. Our results suggest that strain localization, dilation and fluid focusing during structural reactivation could be some of the key factors governing gold mineralization at Laverton.